2006
DOI: 10.2167/cilp100.0
|View full text |Cite
|
Sign up to set email alerts
|

On Language Management in Multinational Companies in the Czech Republic

Abstract: In this paper, we demonstrate the dialectical relationship between micro and macro language planning: macro planning influences micro planning and yet macro planning results (or should result) from micro planning. The relation between the two planning perspectives is illustrated within the framework of Language Management Theory (Jernudd & Neustupný, 1987; Neustupný & Nekvapil, 2003). We deal with the relations between various levels of ‘organised management’, and with the role of the ‘simple, i.e. dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(11 citation statements)
references
References 10 publications
0
8
0
3
Order By: Relevance
“…Macro-management is carried out officially by socalled decision-makers, while micro-management is more informal and consists in the daily management of language by the speakers themselves (Nekvapil, 2006). Both should ideally be in a dialectical relationship: actors manage language on the basis of established standards, but the standards should in turn reflect actual practices and not impose unrealistic constraints on actors (Nekvapil & Nekula, 2006). On the side of management research, several articles published in the late 1990s and early 2000s stated that the language factor had been forgotten by the discipline (Feely & Harzing, 2002;Marschan, Welch, & Welch, 1997).…”
Section: Companies As Actors Of Language Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Macro-management is carried out officially by socalled decision-makers, while micro-management is more informal and consists in the daily management of language by the speakers themselves (Nekvapil, 2006). Both should ideally be in a dialectical relationship: actors manage language on the basis of established standards, but the standards should in turn reflect actual practices and not impose unrealistic constraints on actors (Nekvapil & Nekula, 2006). On the side of management research, several articles published in the late 1990s and early 2000s stated that the language factor had been forgotten by the discipline (Feely & Harzing, 2002;Marschan, Welch, & Welch, 1997).…”
Section: Companies As Actors Of Language Planningmentioning
confidence: 99%
“…Companies are an important, though clearly understudied instance of such micro-level language-planning agency. A potent one, too: internally, companies have the unique ability to manage -and, to some extent, mandate -the language(s) used by their employees in a more or less organized way, notably through their choice of working language and language training (Feely & Harzing, 2003;Nekvapil & Nekula, 2006). Externally, companies are sometimes held responsible for the propagation of English in our societies, a widely observed phenomenon whose excesses may be targeted by macro-level language planning (Dor, 2004;Truchot, 2002).…”
mentioning
confidence: 99%
“…In synergy with these social constructionist and post-national perspectives, scholars have become interested in the reception, interpretation and enactment of LPP goals at meso-and micro-levels, such as within families, language communities or institutions/organisations such as schools and work places (Baldauf, 2006(Baldauf, /2008Hornberger & Johnson, 2007;Nekvapil & Nekula, 2006;Payne, 2006, Siew Kheng Chua, 2006Sims, 2006;Winter & Pauwels, 2006;Zhao & Baldauf, 2010). Research has demonstrated that with increased patterns of mobility there has been a weakening of influence and governance by nation states and an increase in 'cosmopolitan' practices and attitudes which have nurtured the development and performance of complex language repertoires, identities, and fluid multilingual contexts sometimes challenging national and institutional policies (Author 2014;Author, in print;Liddicoat 2009;Sassen 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of institutions have moved to adopt formal policies pertaining to language practices -including that at the level of language choice -in the workplace (e.g., Nekvapil & Nekula, 2006;Lønsmann, 2011;Neeley, 2013;Angouri & Miglbauer, 2014;Gunnarsson, 2014;Hultgren, 2014). Such explicit language policing may be introduced to respond to the changing demands that result from increased globalisation, including the internationalized make-up of a particular institutional community, be it for example a company operating across borders or with greater numbers of migrant professionals, foreign-based clients or partners in other parts of the world, at popular tourist attractions, or at particular institutional programmes within tertiary-level education.…”
Section: Introduction -Overviewmentioning
confidence: 99%